2001
DOI: 10.1002/bit.1130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of media composition on yield values of bacteria growing on binary and ternary substrate mixtures in continuous culture

Abstract: Pseudomonas aeruginosa 142 and a presumed variant were grown axenically in chemostats on salicylate/benzoate or salicylate/glucose binary feeds. Each substrate was supplied at 2, 10, 50, 90, 98, or 100% of the total energy flux. Two experiments were also run with ternary mixtures using the same substrates. Aliquots were transferred to fed-batch reactors receiving the same substrates at the same specific rates as the chemostat, but with one substrate radiolabeled with 14C. Radiolabel incorporated into biomass, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…As seen in Table I, the in vitro enzyme activities in all experiments were much higher than the in vivo speci®c uptake rates required to handle the salicylate entering the chemostat, suggesting a well developed capability to metabolize the substrate over the entire substrate range, even when it contributed only 2% of the energy¯ux. This was consistent with the fact that there was little change in the fate of the carbon in the salicylate over the range of energy¯uxes studied (Rudolph and Grady, 2001). In addition, no salicylate was detected in the euents, with a detection limit of 100 lg/L (Rudolph, 1999).…”
Section: Salicylate and Benzoate Binary Feedssupporting
confidence: 83%
See 4 more Smart Citations
“…As seen in Table I, the in vitro enzyme activities in all experiments were much higher than the in vivo speci®c uptake rates required to handle the salicylate entering the chemostat, suggesting a well developed capability to metabolize the substrate over the entire substrate range, even when it contributed only 2% of the energy¯ux. This was consistent with the fact that there was little change in the fate of the carbon in the salicylate over the range of energy¯uxes studied (Rudolph and Grady, 2001). In addition, no salicylate was detected in the euents, with a detection limit of 100 lg/L (Rudolph, 1999).…”
Section: Salicylate and Benzoate Binary Feedssupporting
confidence: 83%
“…Tests to establish the fate of the benzoate carbon showed that the percentages going to cell mass, carbon dioxide, and soluble The speci®c uptake rate required to remove all of the applied substrate from the chemostat. microbial products were no dierent from those in experiments 10Sa/90Be and 100Be (Rudolph and Grady, 2001), suggesting that the amount of enzyme expressed in experiment 2Sa/98Be was sucient to handle all of the benzoate entering the chemostat. Con®rmation of this can be obtained in Table I, where it can be seen that the activity of catechol 1,2-dioxygenase measured in vitro in experiment 2Sa/98Be was more than 10 times the amount needed in vivo to metabolize all of the benzoate entering the chemostat.…”
Section: Salicylate and Benzoate Binary Feedsmentioning
confidence: 70%
See 3 more Smart Citations